Polybenzimidazole and Phosphonic Acid Groups-Functionalized Polyhedral Oligomeric Silsesquioxane Composite Electrolyte for High Temperature Proton Exchange Membrane. (12th October 2016) - Kim, Sung-Kon
Abstract : Here, we report composite membrane consisting of poly[2, 2′-( m -phenylene)-5, 5′-(bibenzimidazole)] (PBI) and polyhedral oligomeric silsesquioxane functionalized with phosphonic acid groups (PO(OH)2 -POSS) for high temperature proton exchange membrane. 7 phosphonic acid groups are incorporated into the phenyl rings of POSS via bromination in a high yield ( 93%), followed by substitution of the bromine elements by phosphonate ester groups via a Pd(0) catalyzed P–C coupling reaction. Phosphonic acid groups are formed by the hydrolysis of the phosphonate ester groups in hydrobromic acid solution. At a 50 wt% of PA content in the membranes, PBI/PO(OH)2 -POSS composite membrane shows larger proton conductivity of 3.2 × 10 −3 S cm −1 than 2.8 × 10 −3 S cm −1 of PBI membrane at 150°C and anhydrous conditions, owing to the multiple phosphonic acid groups of PO(OH)2 -POSS that can function as proton transport medium at high temperature and low humidity conditions.